2011
DOI: 10.1371/journal.pone.0027087
|View full text |Cite
|
Sign up to set email alerts
|

The PNPLA3 rs738409 148M/M Genotype Is a Risk Factor for Liver Cancer in Alcoholic Cirrhosis but Shows No or Weak Association in Hepatitis C Cirrhosis

Abstract: BackgroundAn isoleucine>methionine mutation at position 148 in the PNPLA3 gene (p.I148M, rs738409) has recently been identified as a susceptibility factor for liver damage in steatohepatitis. Here, we studied whether the PNPLA3 rs738409 polymorphism also affects predisposition to hepatocellular carcinoma (HCC).MethodsWe compared distributions of PNPLA3 genotypes in 80 and 81 Caucasian patients with alcoholic and hepatitis C virus (HCV)-associated HCC to 80 and 81 age- and sex-matched patients with alcohol-rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
97
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(107 citation statements)
references
References 28 publications
(37 reference statements)
1
97
2
1
Order By: Relevance
“…In this study the G allele frequency appears slightly higher in the liver transplant recipient population (29%) than in the general population ($21% to 25%) (14,18,19,24). However, the frequency of GG polymorphism is close to twice the normal population (which is $5%) (19,25), possibly relating to the increased risk of liver disease progression, resulting in a GG enriched population. Although some studies have suggested less of an association of PNPLA-3 polymorphisms with insulin resistance or obesity (14,18,19,26), mechanistic studies have linked glucose metabolism and obesity with PNPLA-3 stimulation and protein production in the insulin sensitive individual (24,27,28).…”
Section: Discussioncontrasting
confidence: 49%
“…In this study the G allele frequency appears slightly higher in the liver transplant recipient population (29%) than in the general population ($21% to 25%) (14,18,19,24). However, the frequency of GG polymorphism is close to twice the normal population (which is $5%) (19,25), possibly relating to the increased risk of liver disease progression, resulting in a GG enriched population. Although some studies have suggested less of an association of PNPLA-3 polymorphisms with insulin resistance or obesity (14,18,19,26), mechanistic studies have linked glucose metabolism and obesity with PNPLA-3 stimulation and protein production in the insulin sensitive individual (24,27,28).…”
Section: Discussioncontrasting
confidence: 49%
“…Interestingly, although PNPLA3 polymorphism has been related to hepatic steatosis in patients with HCV infection, its association with HCC development is less clear with conflicting results. Some studies have demonstrated that the GG genotype effect the risk of HCC development (Falleti et al, 2011;Sato et al, 2014), while most other studies have reported no such association (Nischalke et al, 2011;Guyot et al, 2013;Friedrich et al, 2014). For patients with HBV infection, recent data reported that PNPLA3 polymorphism was independently associated with hepatic steatosis, but not with advanced fibrosis and HCC development (Vigano et al, 2013;Brouwer et al, 2015;Zampino et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that this SNP is related to the impairment of hepatic triglyceride hydrolysis, resulting the accumulation of triglycerides in the hepatocytes . Recent studies have shown an association between rs738409 and HCC development in NASH (Romeo et al, 2008;Valenti et al, 2013;Liu et al, 2014) and ASH (Nischalke et al, 2011;Stickel et al, 2011;Trepo et al, 2012), suggesting a carcinogenic effect by modulating lipid metabolism. However, it is not clear whether this polymorphism affects HCC development in patients with chronic viral hepatitis (Singal et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, only two small-sample case-control studies from Italy [32,61] initially reported a positive association between rs738409[G] and HCC in HCV-infected patients, while at least 2 others did not observe this result [55,56]. Moreover, results obtained from meta-analyses of these studies did not provide firm conclusions [16,53].…”
Section: Pnpla3 and Hepatocellular Carcinomamentioning
confidence: 98%
“…In alcoholic cirrhotic patients, the level of evidence is solid. All initial case-control studies conducted in this population reported significant associations with PNPLA3 variants, with ORs indicating increased risk [55][56][57][58]. Most studies in this field were conducted in Europe and included a homogeneous population of nearly 1,500…”
Section: Pnpla3 and Hepatocellular Carcinomamentioning
confidence: 99%